INDICATORS OF RELIABILITY AND PROBABILITY OF OPERATING CONDITION OF SIGNAL SENSORS OF MICROPROCESSOR TELECOMMUNICATION DEVICES - Art. Ave. Korotkova Larisa Alexandrovna; Assoc. Yusupov Yarashbek Tokhirbaevich; Art. Zhabborov Ave. Alibek Botirkul coals; Ass. Rakhimov Zhamshid Norboy coals (American Journals Publishing, 2024)
This article is devoted to the study of the probabilities of the operating state of a monitoring sensor, control of telecommunications and communication devices by electric current and voltage. In practice, it is necessary to calculate the probability indicators of the functioning of the sensor elements involved in the formation of Uev - output voltage based on the I - primary current, magnetic, thermal and other quantities and parameters.
Keywords: Sensor, signal, control, management,microprocessor, electronic devices, telecommunication, communication, operating state probability.